Context-aware latency reduction protocol for secure encryption and decryption. (2018) - Almiani, Muder; Razaque, Abdul; Aidja, Toufik; Al-Dmour, Ayman
Security is one of the biggest challenges for data communication. As the use of mobile phones has increased, people started using several mobile applications to handle the internet-of-things. On other hand, the frequent use of mobile phones in the business caught the attention of researchers to protect the manufacturers and customers. Handling these issues, several paradigms for encrypting and decrypting the data-outsourcing are proposed. However, there are still new threats that challenge researchers due to new attacking methods and malicious actions of adversaries. Though, the manufacturers have implemented an industry standard to protect the customers' privacy, but existing standards do not provide comfortable zone for the customers, particularly reducing the latency of the emerging applications being used in internet-of-things. In this paper, we introduce context-aware security (ConSec) protocol to support the internet-of-things applications to reduce the latency while encrypting and decrypting the applications. Furthermore, elliptic curve cryptography is used to fully secure the encryption and decryption processes. The proposed method is implemented using Java platform and results are verified and compared with full disk method from the latency perspective.